Use of prophylactic uterotonics during the third stage of labor: a survey of provider practices in community health facilities in Sierra Leone. Issue 1 (December 2016) - Natarajan, Abirami; Ahn, Roy; Nelson, Brett; Eckardt, Melody; Kamara, Jennifer; Kargbo, SAS; Kanu, Pity; Burke, Thomas
Abstract Background Postpartum hemorrhage remains the leading cause of maternal mortality worldwide. Administration of uterotonics during the third stage of labor is a simple and well established intervention that can significantly decrease the development of postpartum hemorrhage. Little is known about the use of prophylactic uterotonics in peripheral health centers, where the majority of normal deliveries occur. The purpose of this study is to assess health provider current practices and determinants to the use of prophylactic uterotonics in Sierra Leone, a country with one of the highest maternal mortality ratios worldwide. Methods This is a mixed methods study using descriptive cross-sectional survey and qualitative interviews in community health facilities in Freetown, Sierra Leone following a comprehensive training on postpartum hemorrhage. Facilities and providers were surveyed between May and June 2014. Qualitative methods were used to identify barriers and facilitators to the use of prophylactic uterotonics. Results A total of 134 providers were surveyed at 39 periphreal health facilities. Thirteen facilities (39 %) reported an inconsistent supply of oxytocin. The majority of facilities (64 %) stored oxytocin at room temperature. Provider level, in-service training, and leadership role were significantly associated with prophylactic uterotonic use. Overall, 62 % of providers reported routine use. Midwives were most likely to routinely administer uterotonics (93 %), followed by community health officers/assistants (78 %), maternal and child health aides (56 %), and state-enrolled community health nurses (52 %). Of the providers who received in-service training, 67 % reported routine use; of those with no in-service training, 42 % reported routine use. Qualitative analysis revealed that facility protocols, widespread availability, and provider perception of utility facilitated routine use. Common barriers reported included inconsistent supply of uterotonics, lack of knowledge regarding timely administration, and provider attitude regarding utility of uterotonics following normal deliveries. Conclusion There is considerable room for improvement in availability and administration of prophylactic uterotonics. Understanding barriers to routine use may aid in developing multifaceted pre-service and in-service training interventions designed to improve routine intrapartum care.